Noninvasive Optical Imaging of Ovarian Metastases Using Cy5-labeled RAFT-c(-RGDfK-) - Zhao-hui Jin; Veronique Josserand; Jesus Razkin; Elisabeth Garanger; Didier Boturyn; Marie-Christine Favrot; Pascal Dumy; Jean-luc Coll (Molecular Imaging)
Our group has developed a new molecular tool based on the use of a regioselectively addressable, functionalized template (RAFT) scaffold, where four cyclic (Arg-Gly-Asp) (cRGD) peptide motifs were grafted. The aim of this study was to determine whether RAFT-c(-RGDfK-) 4 combined with optical imaging could allow noninvasive detection of deep ovarian metastases. Human ovarian adenocarcinoma IGROV1 cells expressing low levels of integrin α v β 3 (the main receptor for the cRGD peptide) were used for in vitro and in vivo assays in combination with Cy5-labeled RAFT-c(-RGDfK-) 4 , cRGD, or RAFT-c(-RβADfK-) 4 . In vivo fluorescence imaging was performed on subcutaneous (SC) tumors and intraperitoneal IGROV1 metastases in nude mice. The accumulation of RGD-Cy5 conjugates in cultured cells or in tumor tissues was examined using confocal laser scanning microscopy. RAFT-c(-RGDfK-) 4 exhibited stronger staining in vitro, enhanced tumor-to-background ratio for SC tumors, and allowed early detection of 1- to 5-mm large intraabdominal nodules using noninvasive optical imaging. Histological study revealed that RAFT-c(-RGDfK-) 4 accumulated into tumor neovasculature but also into tumor cells. Our data demonstrate that a Cy5-labeled RAFT-c(-RGDfK-) 4 is an efficient optical probe for early and noninvasive tumor detection.